An enhanced triplet CNN based on body parts for person re-identificacion - Espinoza J.D. (2018)
This work was supported by grant 234-2015-FONDECYT (Master Program) from Cienciactiva of the National Council for Science,Technology and Technological Innovation (CONCYTEC-PERU).